THE EFFORT TO IMPROVE TEACHERS’PERFORMANCE OF SMA TMI ROUDLATUL QUR’AN IN COMPOSING LESSON PLAN AND EVALUATION INSTRUMENT OF CHARACTER EDUCATION THROUGH WORKSHOP ACADEMIC YEAR 2015/2016 - Budi Raharjo (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2015)
Abstract:Difficulties found in Senior High School (SMA) TMI Roudlatul Qur’an, teachers were not able to integrate character value into their lesson plan and to identify which behaviour must be success indicators of character education. Out of 18 Character value existed, the measurement of students’success as the better change of their behaviour, some only covering observation and lack of triangulation consideration to more accountable result. Worskhop potentially becomes one of the ways to up grade teachers’performance in determining the instrument of character value education, at the same time, train them the way composing lesson plan which integrates character education. This school action research was aimed to carry out workshop at SMA TMI Roudlatul Qur’an of Metro Municipal City, to improve teachers’performance in composing evaluation instrumen of value character education, to improve teachers’performance in composing integrated character value education.The research took place at SMA TMI Roudlatul Qur’an, located at Mulyojati, Metro Barat, Metro Municipal City. It was done in odd semester, continually to one month. Started in early Academic Year 2015/2016, July to August.The researcher concluded that teachers of SMA TMI Roudlatul Qur’an improved their performance well in composing evaluation instrument of value character education and integrated value character lesson plan through workshop. Facts: Workshop process was considered fair 11 teachers, good by 16 teachers, and very good by 12 teachers. At cycle II, the performance of composing evaluation instrument of character education showed 11 teachers were less sufficient performance, 16 teachers were good performance, and 12 teachers were very good. And the performance of composing integrated character value at cycle II showed 8 moderate teachers, 19 good teachers, and 12 excellent teachers.Key words: Workshop, Lesson Plan, Character Education Evaluation